Kryptowaluty — nowy kierunek badań - Srokosz, Witold (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The aim of the article is to identify new areas of legal research on cryptocurrencies. The first cryptocurrency — Bitcoin appeared in 2009. It is therefore a new social phenomenon, however, very dynamically developing and arousing strong emotions. Cryptocurrencies are not a legal tender but they are monetary units which are an abstract measure of value, and certainly can perform all the traditional functions of money. They should be regarded as an alternative currency, community currency, other than regulated e-money, or virtual currency the EBA and the ECB qualifies cryptocurrency as a decentralized virtual currency. Cryptocurrencies should be tested in all three areas of legal regulation — civil, administrative and criminal. In each of these areas such research should take into account the specific nature of the regulation. Dissemination of cryptocurrency can be dangerous for a legal tender and may result in the need for the intervention of the legislature. The findings concerning the legal consequences of the dissemination of cryptocurrency are therefore particularly important.
Keywords: kryptowaluty; kryptowaluty jako pieniądz; regulacje prawne